Modelling microplastics in the River Thames: sources, sinks and policy implications - Whitehead, PG; Bussi, G; Hughes, JMR; Castro-Castellon, AT; Norling, MD; Jeffers, ES; Rampley, CPN; Read, DS; Horton, AA (MDPI, 2021)
With widespread, long-term historical use of plastics and the presence of microplastics in a range of new and existing products, there is rising concern about their potential impacts on freshwater ecosystems. Understanding how microplastics are transported and distributed along river systems is key to assessing impacts. Modelling the main flow dynamics, mixing, sedimentation and resuspension processes is essential for an understanding of the transport processes. We use the new, processed based, dynamic, integrated catchments (INCA) microplastics model and apply this to the whole of the freshwater catchment of the River Thames, UK, to evaluate inputs, loads and concentrations along the river system. Recent data from UK water industry studies on microplastics in effluent discharges and sewage sludge disposal has been utilised to drive the INCA microplastics model. Predicted concentrations and microplastic loads moving along the river system are shown to be significant, with a build-up of concentrations along the river, with increasing deposition on the riverbed. The potential impacts on aquatic ecosystems are evaluated and a review of policy implications is explored.